PELATIHAN HYPNOPRESSURE UNTUK MEMPERLANCAR ASI EKSKLUSIF PADA IBU USIA REMAJA - Risti Linta Chumaira; Fitriani Fitriani (LPPM AN Nuur, 2026)
Background: Breast milk (breast milk) is the best natural food that a mother can give to her baby. Breastfeeding is influenced by age, the younger the mother, the smaller the breastfeeding tends to be. Consistent milk production and confidence in breastfeeding are essential for the success of exclusive breastfeeding. Hypnopressure is one of the methods that can increase and maintain breast milk production. Purpose: The purpose of this intervention is to provide hypnopressure education on the problem of smooth breastfeeding in adolescent mothers. Method: The activity was carried out in Menduran Village, the working area of the Brati Health Center, with 10 teenage mothers participating. The stages include problem identification, planning, team development, and implementation. Education was carried out using the lecture method, the media used, namely SOPs related to hypnopressure techniques, acupressure meridian point leaflets, and sound systems. Results: The results of the pre-test showed that 6 participants (60%) were still not fluent in providing exclusive breastfeeding. After 7 days of training, the results of the post test showed an increase in the smoothness of Exclusive Breastfeeding, namely 9 participants (90%). Conclusion: Hypnopressure can improve the smoothness of breastfeeding so that this intervention can be an alternative to be given to adolescent mothers to be useful for the success of exclusive breastfeeding.